Una breve introducción a la invención del niño delincuente - Belén Vázquez, María (Archivos de criminología, seguridad privada y criminalística, 2021)
This brief article pretends to review how throughout the history and the perspective of each society, childhood has been conceived – especially the underprivileged -, and how the situation of this childs in conflict with the criminal law was addressed.